Contesting sociocomputational norms: Computer programming instructors and students’ stancetaking around refactoring - Fong, Morgan M.; DeLiema, David; Flood, Virginia J.; Aalst, Oia Walker-van (International journal of computer-supported collaborative learning, 2025)
Working solutions to problems are not definitive end points. As a result, code that is technically correct can still be treated as needing revising – a practice in computer programming known as refactoring. We document how late elementary to middle school students and their undergraduate instructors weigh the possibility of refactoring working code in an informal summer computer science workshop. We examined a 20-min stretch of classroom activity in which multiple coding approaches were explicitly evaluated as alternative routes to the same code output. Our theoretical framework draws on the stance triangle, amplifying and attenuating inequity, and an extension of sociomathematical norms. Using the method of interaction analysis, we transcribed and analyzed stretches of talk, gesture, and action during whole class dicourse and small group interactions involving 4–6 students. We investigated how instructors and students introduced, characterized, applied, and contested sociocomputational norms through stancetaking in classroom discourse, which shaped whose voices contributed to the discussion and whose ideas were treated as impactful and praiseworthy in the classroom. Because it is within these discourse spaces that instructors and students interpret and reinterpret sociocomputational norms about what is valued in programming approaches, educational researchers and teachers might attend to these conversation dynamics as one route to fostering more supportive and inclusive learning spaces.